Consumption of Walnuts in Combination with Other Whole Foods Produces Physiologic, Metabolic, and Gene Expression Changes in Obese C57BL/6J High-Fat–Fed Male Mice. Issue 9 (3rd August 2016) - Luo, Ting; Miranda-Garcia, Omar; Adamson, Allysa; Hamilton-Reeves, Jill; Sullivan, Debra K; Kinchen, Jason M; Shay, Neil F
Abstract: Background: Although a reductionist approach has sought to understand the roles of individual nutrients and biochemicals in foods, it has become apparent that there can be differences when studying food components in isolation or within the natural matrix of a whole food. Objective: The objective of this study was to determine the ability of whole-food intake to modulate the development of obesity and other metabolic dysfunction in mice fed a high-fat (HF), Western-style obesogenic diet. To test the hypothesis that an n–3 (ω-3) polyunsaturated fatty acid-rich food could synergize with other, largely polyphenol-rich foods by producing greater reductions in metabolic disease conditions, the intake of English walnuts was evaluated in combination with 9 other whole foods. Methods: Eight-week-old male C57Bl/6J mice were fed low-fat (LF; 10% fat) and HF control diets, along with an HF diet with 8.6% (wt:wt) added walnuts for 9 wk. The HF control diet contained 46% fat with added sucrose (10.9%, wt:wt) and cholesterol (1%, wt:wt); the added sucrose and cholesterol were not present in the LF diet. Other groups were provided the walnut diet with a second whole food—raspberries, apples, cranberries, tart cherries, broccoli sprouts, olive oil, soy protein, or green tea. All of the energy-containing whole foods were added at an energy level equivalent to 1.5 servings/d. Body weights, food intake, and glucose tolerance were determined. Postmortem, serum lipids and inflammatory markers, hepatic fat, gene expression, and the relative concentrations of 594 biochemicals were measured. Results: The addition of walnuts with either raspberries, apples, or green tea reduced glucose area under the curve compared with the HF diet alone (−93%, −64%, and −54%, respectively, P < 0.05). Compared with HF-fed mice, mice fed walnuts with either broccoli sprouts or green tea (−49% and −61%, respectively, P < 0.05) had reduced hepatic fat concentrations. There were differences in global gene expression patterns related to whole-food content, with many examples of differences in LF- and HF-fed mice, HF- and walnut-fed mice, and mice fed walnuts and walnuts plus other foods. The mean ± SEM increase in relative hepatic concentrations of the n–3 fatty acids α-linolenic acid, eicosapentanoic acid, and docosapentanoic acid in all walnut-fed groups was 124% ± 13%, 159% ± 11%, and 114% ± 10%, respectively ( P < 0.0001), compared with LF- and HF-fed mice not consuming walnuts. Conclusions: In obese male mice, walnut consumption with an HF Western-style diet caused changes in hepatic fat concentrations, gene expression patterns, and fatty acid concentrations. The addition of a second whole food in combination with walnuts produced other changes in metabolite concentrations and gene expression patterns and other physiologic markers. Importantly, these substantial changes occurred in mice fed typical amounts of intake, representing only 1.5 servings each food/d.